To Estimate The Prevalence Of Adenomyosis And Its Correlation With Benign Endometrial Lesions In Tertiary Care Center (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Adenomyosis is a prevalent gynecological disorder among women with no specified causes. It is characterized by non-specificsymptoms, and can present itself as abnormal uterine bleeding, abdominal pain, menstrual disorders. The objective of this study is to correlateadenomyosis with benign endometrial lesions like Leiomyoma, Benign endometrial polyp, Endometrial hyperplasia and to evaluate theprevalence of adenomyosis among the hysterectomized specimens.Material & methods: This retrospective study was conducted in the Department of Pathology in Meenakshi Medical College Hospital andResearch Institute, a tertiary care center in Kanchipuram, from January 2020 to April 2022. A total of 247 patients who underwenthysterectomy surgery and diagnosed as Adenomyosis and other benign endometrial lesions were studied. After reviewing the patients data,the main complaints as well as benign endometrial lesions associated with adenomyosis, were examined. Finally all the data were analyzedusing statistical tests.Results: In our study, the prevalence of adenomyosis was 53.03% and it was most frequently observed in the fourth decade (61.83% ).Adenomyosis was more prevalent in women with parity 2 and parity 3, and the most common complaint was Abnormal Uterine Bleeding(73% ). Leiomyoma (66.6%), Benign Endometrial polyp (19.2%), and Endometrial hyperplasia(14.1%) were the most common endometriallesions associated with adenomyosis. Among the Benign endometrial lesions, Leiomyoma had the highest correlation with Adenomyosis.Conclusions: The histomorphological study of endometrial lesions is necessary for making a final diagnosis of Adenomyosis, because it isone of the major causes of abnormal uterine bleeding in perimenopausal women.